Accessing care services after sexual violence: A systematic review exploring experiences of women in South Africa - Moreoagae B. Randa; Julie McGarry; Sarah Griffiths; Kathryn Hinsliff-Smith (AOSIS, 2023)
Background: Sexual violence against women is a global phenomenon. This is a particular issue in South Africa, where it is estimated with evidence provided that up to half of all women will encounter gender-based and/or sexual violence from a partner during their lifetime. Therefore, evidence suggests that addressing the needs of women in South Africa is a priority. Objective: This qualitative review aimed to explore the experiences of women seeking care from first contact healthcare facilities in South Africa after sexual violence and during follow-up care. Method: This systematic review was conducted using the PRISMA checklist for systematic reviews and in line with a published protocol (PROSPERO, CRD42019121580) and searched six relevant databases in 2022. A total of 299 sources were screened, with 5 forming the overall synthesis. Results: Two synthesised themes of women's experiences emerged at the time of reporting and during attendance at follow-up healthcare services. Conclusion: South Africa does have an established legal framework for prosecution and can provide support for survivors of sexual violence through established Thuthuzela Care Centres (TCCs). The review identifies that survivors' needs are not clearly established when seeking medical attention initially nor identifying support or appropriate pathways. Contribution: The review has the potential to characterise the support available for women, the type and nature of sexual violence and interventions that may be used by healthcare professionals to support survivors especially during follow-up care.